Anxiety-like behaviors in mice lacking GIT2 - Schmalzigaug, Robert (2008)
G protein-coupled receptor kinase-interactor 2 (GIT2) is a signaling scaffold protein that also functions as GTPase-activating protein (GAPs) for ADP-ribosylation factor (Arf) small GTP-binding proteins. GIT2 has been implicated in the regulation of G protein-coupled receptor trafficking and cell adhesion and migration. To evaluate possible neurobehavioral functions of GIT2 in vivo, we evaluated GIT2-knockout (KO) mice for abnormalities in emotionality and mood. Male and female GIT2-KO mice presented with anxiety-like behaviors in the zero-maze and light-dark emergence tests. Immobility times in tail suspension were reduced in GIT2-KO males, but were normal in GIT2-KO females. Hence, GIT2-KO mice display anxiety-like behavior in an absence of depressive-like responses.